Teacher Skills to Provide GMIM Ranoketang Elementary Students’ Reinforcement - Romi Mesra; Rus Yandi; Veron Gilbert Walintukan; Meffi Andrina Mangangantung; Anggreiny Tampongangoy; Natasha Indah Putri Sumahaf; Yesika Pangkey (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In the learning process at school, a teacher must have the skills to provide reinforcement in teaching in order to achieve the expected learning goals. The research is intended to explain the use of teacher reinforcement skills in learning at GMIM Ranoketang Elementary School. The research was conducted at GMIM Ranoketang Elementary School. The research is qualitative research with a descriptive research design. Data collection methods used observation, interviews, and documentation to obtain data. Research findings indicate that instructors use learning skills components, which involve verbal and nonverbal reinforcement. Verbal reinforcement is used to provide appreciation in the form of words and sentences. Nonverbal reinforcement is applied with Submitted: gestures and body movements, tactile reinforcement, entertaining activities, reinforcement in the form of symbols or items, and partial reinforcement. Furthermore, instructors use a reinforcement approach in learning, which includes reinforcement for specific people, reinforcement for groups, rapid reinforcement, and changes in the implementation of reinforcement. In conclusion, a teacher must understand and master the skills of providing reinforcement in order to increase the enthusiasm and motivation of students in the teaching and learning process and also to achieve learning goals.